Equilibrium, thermodynamic and kinetics studies on adsorption of eosin Y and red X-GRL from aqueous solution by treated rice husk - Saideh Fatemeh Shafeii Darabi; Nader Bahramifar; Mohamad Ali Khalilzadeh (Journal of Applied Research in Water and Wastewater, 2018)
Present study explored the adsorptive characteristics of eosin Y and red X dyes from aqueous solution onto treated rice husk (TRH). Batch experiments were carried out to determine the influence of parameters likes initial pH, adsorbentdose, contact time and initial concentration on the removal of eosinY and red X. The adsorption kinetics of the two dyes on to TRH was found to follow pseudo-second-order kinetic model. The equilibrium data is successfullyfitted to the Freundlich and Langmuir adsorption isotherm for eosin Y and red X, respectively. The thermodynamic analysis indicated that the sorption process was endothermic for eosin Y and exothermic for red X and the negative value of change in Gibbs free energy indicated feasible and spontaneous adsorption for both of dyes. The removal percentage of dyeswas about 90% (q e= 31.72 mgg-1) for eosin Y and 93.44 % for red X(qe=32.44mgg-1). Overall, the present findings suggest that this environmentally friendly, efficient and low-cost adsorbent is useful for the removal of eosin Y and red X from aqueous solution.